2018
DOI: 10.1136/openhrt-2017-000687
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pharmacist’s intervention in the management of cardiovascular diseases

Abstract: The pharmacist may play a relevant role in primary and secondary prevention of cardiovascular diseases, mainly through patient education and counselling, drug safety management, medication review, monitoring and reconciliation, detection and control of specific cardiovascular risk factors (eg, blood pressure, blood glucose, serum lipids) and clinical outcomes. Systematic reviews of randomised controlled and observational studies have documented an improved control of hypertension, dyslipidaemia or diabetes, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 42 publications
(43 reference statements)
5
100
0
3
Order By: Relevance
“…However, over the past few years, GP has faced increased workload due to multiple reasons including the increase in population and average lifespan, increased prevalence of long‐term medical conditions, frequency of diseases and complexity of treatment regimen . Pharmacists by virtue of patient education, medicine reconciliation and management of CVD risk factors can play an important role in the primary prevention of CVD that can help ease the burden on primary care physicians (PCP).…”
Section: Introductionmentioning
confidence: 99%
“…However, over the past few years, GP has faced increased workload due to multiple reasons including the increase in population and average lifespan, increased prevalence of long‐term medical conditions, frequency of diseases and complexity of treatment regimen . Pharmacists by virtue of patient education, medicine reconciliation and management of CVD risk factors can play an important role in the primary prevention of CVD that can help ease the burden on primary care physicians (PCP).…”
Section: Introductionmentioning
confidence: 99%
“…An overview of this body of research has been summarized by Omboni and Caserini. 1 The authors have concluded that "A common finding of the systematic reviews is that greater involvement of pharmacists in activities directed to the patients and collaboration with other health care professionals in a team may provide an enhanced effect on various outcomes and may ultimately positively affect public health." Furthermore, a systematic review by Santschi et al 2 evaluated 39 controlled trials of pharmacists' care for patients with CVD in ambulatory settings.…”
Section: Pharmacists' Impact: the Evidencementioning
confidence: 99%
“…Pharmacists who directly engage patients to provide guidance on medication use, along with follow-up to monitor patients' progress, can support high levels of adherence to medications, whereas physicianpharmacist collaboration can lead to better prescribing and monitoring of patients. 1,3,4 Cardiometabolic disease begins with insulin resistance, progressing to metabolic syndrome, prediabetes, and ultimately to cardiovascular disease and type 2 diabetes. 5 Cardiometabolic complications have been increasing owing to the increasing prevalence of contributing disease states (e.g., hypertension, diabetes, and obesity).…”
Section: Pharmacists' Impact: the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacist interventions have been shown to consistently benefit the management of hypertension, hyperlipidemia, diabetes, and smoking cessation. 10 Patients who have a pharmacist involved in their blood pressure management show statistically significant improvements in their medication adherence, disease-state knowledge, and blood pressure control. 11 Hunt et al 12 found that pharmacist intervention improved the percentage of patients whose blood pressure was controlled from 44% to 62%.…”
mentioning
confidence: 99%